Geobiological interactions of archaeal populations in acidic and alkaline geothermal springs of Yellowstone National Park, WY, USA - Beam, Jacob Preston (Montana State University - Bozeman, College of Agriculture, 2015)
Microbial communities in high-temperature acidic and alkaline geothermal springs contain abundant, novel Archaea whose role in biogeochemical cycling and community function in microbial mats is not described. This thesis utilized a complementary suite of analyses that included aqueous and solid phase geochemistry, community genomics, phylogenomics, targeted 16S rRNA gene sequencing, community transcriptomics, and microscopy to elucidate the role of novel archaeal populations in acidic sulfur and iron rich hot springs in Norris Geyser Basin, Yellowstone National Park (YNP), and alkaline microbial 'streamer' communities in Lower Geyser Basin, YNP. Novel members of the archaeal phylum, Thaumarchaeota were identified in oxic iron oxide mats and hypoxic elemental sulfur sediments in acidic geothermal springs. These two different groups of Thaumarchaeota likely utilize organic carbon as electron donors and exhibited metabolic capacities based on the presence and absence of oxygen (e.g., heme copper oxidases). The assembly and succession of iron oxide mats in acidic geothermal springs showed later colonization (> 40 d) of Thaumarchaeota. Early colonizers (< 7 d) of Fe(III)-oxide mats include Hydrogenobaculum spp. (Aquificales) and the iron-oxidizing Metallosphaera yellowstonensis (7 - 14 d), which accrete copious amounts of Fe(III)-oxides. Interaction of Hydrogenobaculum and M. yellowstonensis is important to mat formation and subsequent later colonization of heterotrophic archaea (> 40 d). The succession of these communities follows a repeatable pattern, which exhibits interplay among oxygen flux, hydrodynamics, and microbial growth. The biogeochemical and micromorphological signatures may be important for the interpretation of ancient Fe(III)-oxide geothermal deposits. Interactions between Archaea and Aquificales are also important in oxic, alkaline 'streamer' communities, which contain a novel Aigarchaeota population and Thermocrinis spp. This Aigarchaeota population (Candidatus "Calditenuis aerorheumensis") exhibits a filamentous morphology and was intricately associated with Thermocrinis spp. C. aerorheumensis is an aerobic chemoorganotroph. Oxygen is the predominant electron acceptor of C. aerorheumensis, and mRNA transcripts were elevated for heme copper oxidase complexes. Organic carbon electron donors may come from bacteria in close proximity and/or dissolved organic carbon. Archaeal interactions with Aquificales contribute to higher-order level properties (e.g., biomineralization, metabolite sharing) that are important in the formation of hot spring microbial mats and streamer communities.
Keywords: Hot springs; Archaebacteria; Microbial mats